Effect of Mg Oxide nanoparticles on sulphur vulcanisation of natural rubber - Qamarina M Siti Nor; Kawahara Seiichi (Journal Rubber Research, 2014)
Magnesium oxide (MgO) nanoparticles were introduced in natural rubber(NR) as an activator to investigate its effect on NR vulcanisates. The MgO nanoparticles were mixed in a ratio of 0-20 p.h.r. before curing at 150dC. Results of cure time and torque showed that at 12 and 20 p.h.r. loadings, acceptable cure characteristics to that of the control compound, 2 p.h.r. zinc oxide (ZnO) were exhibited. Crosslink density of the vulcanisates, determined by the swelling method confirmed that the MgO nanoparticles intensified the formation of crosslinking. Dispersion of the MgO nanoparticles observed by focused ion-beam/scanning electron microscopy (FIB/SEM) and transmission electron microscopy (TEM) indicated that aggregates of complexes distributed throughout the rubber matrix is consistent with the MgO nanoparticle loading and were well correlated to the mechanical properties achieved. These findings offer an alternative route for vulcanisation formulation of NR.
Keywords: Activator; Characterisation; MgO nanoparticles; Rubber; Sulphur vulcanisation